Neutralizing antibodies against flaviviruses, Babanki virus, and Rift Valley fever virus in Ugandan bats. Issue 1 (1st January 2018) - Kading, Rebekah C.; Kityo, Robert M.; Mossel, Eric C.; Borland, Erin M.; Nakayiki, Teddie; Nalikka, Betty; Nyakarahuka, Luke; Ledermann, Jeremy P.; Panella, Nicholas A.; Gilbert, Amy T.; Crabtree, Mary B.; Peterhans, Julian Kerbis; et al.
ABSTRACT: Introduction: A number of arboviruses have previously been isolated from naturally-infected East African bats, however the role of bats in arbovirus maintenance is poorly understood. The aim of this study was to investigate the exposure history of Ugandan bats to a panel of arboviruses. Materials and methods: Insectivorous and fruit bats were captured from multiple locations throughout Uganda during 2009 and 2011–2013. All serum samples were tested for neutralizing antibodies against West Nile virus (WNV), yellow fever virus (YFV), dengue 2 virus (DENV-2), Zika virus (ZIKV), Babanki virus (BBKV), and Rift Valley fever virus (RVFV) by plaque reduction neutralization test (PRNT). Sera from up to 626 bats were screened for antibodies against each virus. Results and Discussion:  Key findings include the presence of neutralizing antibodies against RVFV in 5/52 (9.6%) of little epauletted fruit bats ( Epomophorus labiatus ) captured from Kawuku and 3/54 (5.6%) Egyptian rousette bats from Kasokero cave. Antibodies reactive to flaviviruses were widespread across bat taxa and sampling locations. Conclusion: The data presented demonstrate the widespread exposure of bats in Uganda to arboviruses, and highlight particular virus-bat associations that warrant further investigation.